Policies For The Implementation of Bus Rapid Transit (BRT) in an Effort To Reduce Traffic Congestion in The City of Cirebon - Saeful Bahri; Moh. Taufik Hidayat (International Journal of Social Service and Research, 2026)
Urban traffic congestion and the declining effectiveness of public transportation are among the main challenges in managing mobility in the city of Cirebon. In response to these conditions, the Cirebon City Government developed a Bus Rapid Transit (BRT) system as an alternative public transportation option, which was expected to improve the quality of mobility services for the public while reducing dependence on private vehicles. However, BRT operations were ultimately suspended in 2026 due to various issues affecting the sustainability of the service. This study aims to analyze the implementation of the Bus Rapid Transit (BRT) policy in Cirebon City, identify the factors that have prevented the policy from achieving the desired effectiveness in public transportation and reducing traffic congestion, and formulate directions for reformulating a more adaptive and sustainable public transportation policy. The study employs a qualitative method with a public policy approach. Data were collected through interviews, observations, and document analysis, and were analyzed using James E. Anderson’s public policy cycle theory, which encompasses the policy agenda, policy formulation, policy adoption, policy implementation, and policy evaluation. The research findings indicate that the primary issue with Cirebon City’s BRT does not lie in low public demand for public transportation, but rather in the mismatch between policy design and community mobility patterns, weak integration of transportation services, high reliance on local subsidies, and insufficient governance and sustainability of operational funding. These conditions have prevented the policy objectives of promoting a shift in transportation modes and reducing the dominance of private vehicles from being fully achieved. The reformulation of public transportation policy should focus on data-driven mapping of public mobility, the development of an integrated transportation system, the utilization of digital technology, the strengthening of sustainable financing schemes, and the integration of public transportation with urban spatial planning.